Rockets: Defying Gravity - Anne Drozd (First Second, 2018)
Every volume of Science Comics offers a complete introduction to a particular topic$1 (Bdinosaurs, coral reefs, the solar system, volcanoes, bats, flying machines, and many more. These gorgeously illustrated graphic novels offer wildly entertaining views of their subjects. Whether you're a fourth grader doing a natural science unit at school or a thirty-year-old with a secret passion for airplanes, these books are for you! This volume: In Rockets we explore the 2,000 years that rockets have been in existence. We dive into Newton's Laws of Motion$1 (Blearning all about gravity, force, acceleration, and the history of rockets made in the past and rockets to be made in the future!s
Keywords: Narrative Non-Fiction -- Narrative Non-Fiction